An Unmet Need in Healthcare Leadership: A Survey of Practicing Physicians’ Perspectives on Healthcare Delivery Science Education - Weeks K (Journal of Healthcare Leadership, 2020)
Kristin Weeks,1 Morgan Swanson,1 Hayley Hansen,2 Katherine Merritt,2 Joseph Nellis,3 Mary Charlton,4 Alan Reed5 1Medical Scientist Training Program, Carver College of Medicine, Iowa City, IA, USA; 2Carver College of Medicine, Iowa City, IA, USA; 3Department of Surgery, Duke University, Durham, NC, USA; 4Department of Epidemiology, University of Iowa, Iowa City, IA, USA; 5Department of Surgery, University of Iowa Hospitals and Clinics, Iowa City, IA, USACorrespondence: Alan ReedDepartment of Surgery, University of Iowa Hospitals and Clinics, SE 427 GH, 200 Hawkins Drive, Iowa City, IA 52242, USATel +1 319-356-0537Email alan-reed@uiowa.eduBackground: Healthcare delivery science education (HDSE) is increasingly needed by physicians balancing clinical care, practice management, and leadership responsibilities in their daily lives. However, most practicing physicians have received little HDSE in undergraduate through residency training. The purpose of this study is to 1) quantify the perception of the need for HDSE and interest in HDSE among a diverse sample of physicians, and 2) determine if perspectives on HDSE vary by specialty, rurality, and years in practice.Methods: Using a cross-sectional, single state, mailed questionnaire, we surveyed 170 physicians about their perspectives on HDSE and interest in an HDSE program. Descriptive statistics and a multivariable logistic regression are presented.Results: Among the 70.5% of responding eligible physicians, 75% of physicians had less HDSE than they would like and 90% were interested in obtaining more HDSE. Thirty-five percent of physicians were interested in joining the described HDSE program. The most prevalent barriers to obtaining HDSE were a lack of time and existing programs. Physician perspectives were similar across specialties, years in practice, and rurality.Conclusion: There is a high unmet need for HDSE among physicians. Diverse and innovative HDSE programming needs to be developed to meet this need. Programming should be developed not only for physicians but also for undergraduate through residency training programs.Keywords: healthcare delivery science, management, policy, education, rurality